Optimalisasi Pengembangan Kompetensi ASN di Kementerian Agama: Integrasi Manajemen Strategis, Motivasi, dan Teknologi dalam Perspektif Reformasi Birokrasi - Apriansyah, Agus; Ferunika, Ferunika; Nirvadiana, Nirvadiana (Tatar Pasundan: Jurnal Diklat Keagamaan, 2025)
The development of civil servants’ (ASN) competencies is a fundamental pillar for supporting bureaucratic reform and improving the quality of public services. This study aims to analyze strategies for optimizing competency development services for ASN at the Research and Development and Training Agency of the Ministry of Religious Affairs, emphasizing the role of strategic management, ASN motivation, and technology integration. Employing a qualitative approach through a systematic literature review, this study examines academic articles, policy reports, and official statistical data from the last five years, reinforced by SWOT analysis and data triangulation. Theoretical perspectives of strategic management and change management serve as analytical frameworks to understand the interrelation among variables. The findings reveal that the application of strategic management through needs-based planning and evaluation instruments such as the Balanced Scorecard enhances training effectiveness; intrinsic motivation of ASN has a stronger influence than extrinsic incentives in fostering participation; and the use of e-learning technologies increases training access and participation up to 90%, although challenges of digital literacy remain. Moreover, the rise in ASN participation in training is strongly linked to policy reforms that mandate competency development as part of bureaucratic transformation. This study recommends an integrative strategy that synergizes strategic management, motivation, and digital technology to support systemic transformation of ASN competency development services. Academically, future research should include quantitative studies to empirically test variable relationships, comparative analyses across government institutions, and the development of an integrative theoretical framework combining change management, work motivation, and digital learning theories. These findings are expected to contribute to the academic literature while serving as practical guidance for policymakers in accelerating competency-based bureaucratic reform. Keywords: competency development; strategic management; motivation; e-learning; bureaucratic reform